Breaking out of silos: using classroom videos for cross-disciplinary and cross-methodological examinations of teaching qualities - Luoto, Jennifer M.; Klette, Kirsti; Jentsch, Armin (School effectiveness and school improvement, 2025)
This editorial introduces the special issue "Beyond Fragmentation: Using Classroom Videos for Cross-Disciplinary and Cross-Methodological Examinations of Teaching Qualities." The special issue focuses on how different classroom observation frameworks construct findings of teaching quality of a set of video-recorded lessons in mathematics and in language arts from Norwegian eighth-grade classrooms (approximately 14-year-old students). We give an overview of the traditions of analyzing teaching quality within classroom observation studies and how the frameworks in the contributing papers relate to these traditions. Finally, we present the lessons on which all contributors have focused.